Investigation of the effect of stator resistance on direct torque control and application of permanent magnet synchronous motor - Bozkurt, Ebubekir; Polat, Mehmet (Gumushane University, 2022)
Permanent magnet synchronous motors are a type of motor that is becoming more and more popular due to some superior features together with the technological developments in power electronics. The fact that these motors can produce maximum torque even at zero speed, low maintenance costs and high power/weight ratio has increased their use. In this study, the direct torque control method from vector control methods was used. This method has been investigated by considering the change in the stator winding resistance caused by the temperature increase depending on the operation of the motor and has been applied to a permanent magnet synchronous motor by using a voltage-sourced voltagecontrolled inverter circuit. The modeling of the electric motor has done with the d-q model and this model has used in the simulation study. In order to realize the direct torque control of the motor, torque and flux calculations have been made using the current and voltage data applied to the motor. The obtained flux and torque errors have been applied as input to the hysteresis comparator. The switching strategies in the pulse width modulation method used in the inverter control have realized the torque and speed control of the permanent magnet synchronous motor by using the data obtained from the hysteresis output. The variation of winding resistance with temperature and its effect on different speeds and torque control of the motor has been investigated by keeping all other motor parameters constant. The effect of the stator winding resistance on the speed and torque control of the motor has been shown in simulation studies. © 2022, Gumushane University. All rights reserved.
Doğrudan moment kontrolüne stator direncinin etkisinin incelenmesi ve sürekli mıknatıslı senkron motora uygulaması
Keywords: Direct torque control; Effect of winding resistance; Modelling; Permanent magnet synchronous motor; Speed control